Is Changing Hospitals for Revision Total Joint Arthroplasty Associated With More Complications? - Dy, Christopher J. (Springer US, 2014)
BACKGROUND: Many patients change hospitals for revision total joint arthroplasty (TJA). The implications of changing hospitals must be better understood to inform appropriate utilization strategies. QUESTIONS/PURPOSES: (1) How frequently do patients change hospitals for revision TJA? (2) Which patient, community, and hospital characteristics are associated with changing hospitals? (3) Is there an increased complication risk after changing hospitals? METHODS: We identified 17,018 patients who underwent primary TJA and subsequent same-joint revision in New York or California (1997–2005) from statewide databases. Medicare was the most common payer (56%) followed by private insurance (31%). We identified patients who changed hospitals for revision TJA and those who experienced in-hospital complications. Patient, community, and hospital characteristics were analyzed to determine predictors for changing hospitals for revision TJA and the effect of changing hospitals on subsequent complications. RESULTS: Thirty percent of patients changed hospitals for revision. Older patients were less likely to change hospitals (odds ratio [OR], 0.84; 95% confidence interval [CI], 0.73–0.96); no other patient characteristics were associated with changing hospitals. Patients who had index TJA at the highest-volume hospitals were less likely to change hospitals (OR, 0.52; 95% CI, 0.48–0.57). Overall, changing hospitals was associated with higher complication risk (OR, 1.19; 95% CI, 1.03–1.39). Changing to a lower-volume hospital (6% of patients undergoing revision TJA) was associated with a higher risk of complications (OR, 1.36; 95% CI, 1.05–1.74). A post hoc number needed-to-treat analysis indicates that 234 patients would need to be moved from a lower volume hospital to a higher volume hospital to avoid one overall complication event after revision TJA. CONCLUSIONS: Although the complication risk was higher if changing hospitals, this finding was sensitive to the type of change. Our findings build on the existing evidence of a volume-outcomes benefit for revision TJA by examining the effect of volume in view of potential patient migration. LEVEL OF EVIDENCE: Level III, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.